(untitled) (Al-Farooq Journal of Sciences, 2026)
The integration of geochemistry education with green technology, sustainable resource management techniques, and environmental sustainability concepts is known as green geochemical education. Due to issues with groundwater quality, petroleum operations, environmental pollution, climate change, and sustainable resource use, Libya has a greater need for environmentally conscious education. Current studies conducted in Libya indicate that there is an association between sustainability and geoscience education and development, albeit to a small extent. Education in sustainability through geochemistry present possibilities for incorporating green principles within geochemical education, laboratories, and research. Inclusion of green learning practices within the realm of geochemistry can foster awareness among learners, instill sustainable practices in the lab, and help develop future geochemists who will be able to face environmental issues. The principles, uses, prospects, difficulties, and potential future paths of green geochemical education in Libya are all examined in this paper.